2014
DOI: 10.1002/jbmr.2207
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Components of Body Composition and Scoliosis: A Prospective Cohort Study Reporting Differences Identifiable Before the Onset of Scoliosis

Abstract: There is an increasing body of research suggesting that low body weight is associated with scoliosis, but this is based on case-control studies, which are prone to bias. No studies have investigated the components of body weight: fat and lean mass. We have therefore carried out the first population-based prospective study of the association between fat and lean mass at age 10 years assessed by dual-energy X-ray absorptiometry (DXA), with presence of scoliosis at age 15 years using the Avon Longitudinal Study o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
85
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(102 citation statements)
references
References 42 publications
8
85
1
Order By: Relevance
“…For FLI, controls and AIS group both had significant correlations with all body composition parameters, but the correlations except for %SMM were again weaker in the AIS group. 13.89 AE 2.09 kg, P ¼ 0.035) than normal controls, and they remained significant after adjusted for physical activity level (Table 5). AIS girls also had numerically lower right leg and left leg lean mass, but the difference did not reach statistical significance (P ¼ 0.051 and 0.062 respectively) ( Table 5).…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…For FLI, controls and AIS group both had significant correlations with all body composition parameters, but the correlations except for %SMM were again weaker in the AIS group. 13.89 AE 2.09 kg, P ¼ 0.035) than normal controls, and they remained significant after adjusted for physical activity level (Table 5). AIS girls also had numerically lower right leg and left leg lean mass, but the difference did not reach statistical significance (P ¼ 0.051 and 0.062 respectively) ( Table 5).…”
Section: Resultsmentioning
confidence: 61%
“…11,12 These limited studies have reported conflicting findings with relatively small sample size. Recently, a large prospective cohort study has reported that decrease in leptin, lean, and fat mass was associated with increased risk of scoliosis in adolescents, 13 which provided further evidence supporting the potential link between leptin, abnormal body composition, and AIS. We speculated that the altered leptin bioavailability in AIS girls could affect the subsequent physiological functions of leptin, including the regulation of energy metabolism and body composition.…”
mentioning
confidence: 97%
“…Also, analysis by BMI (body mass index) did not alter the results. This is of note as it has been shown that a low BMI can increase the chance of the development of scoliosis (Clark et al 2014) and thus, by inference, torso asymmetry.…”
Section: Discussionmentioning
confidence: 80%
“…On the contrary, low BMI and fat percentage might cause scoliosis resulting in a deterioration of spinal alignment. In this regard, Clark et al (2014) aimed to identify whether body composition analysis can be used for predicting scoliosis before the onset of clinically detected scoliosis. They showed a negative correlation between BMI and scoliosis refl ecting of combination of reduced fat mass and lean mass and with a %20 reduced risk of scoliosis per SD increase BMI.…”
Section: Discussionmentioning
confidence: 99%
“…They showed a negative correlation between BMI and scoliosis refl ecting of combination of reduced fat mass and lean mass and with a %20 reduced risk of scoliosis per SD increase BMI. Therefore, it can be thought that the measurement of spinal curvature and body composition analysis could be good parameters to detect and prevent injuries, and these measurements should be part of the anthropometric analysis [17].…”
Section: Discussionmentioning
confidence: 99%